Document and Inferential Analysis of Imam Reza's Narration on the Rational Argument for Caution - Sayyid Ali Delbari (آموزه‌‌های فلسفه اسلامي)
Document and Inferential Analysis of Imam Reza's Narration on the Rational Argument for Caution Theology is the most important subject within religious knowledge, and numerous narrations have addressed its various dimensions. This article analyzes both the document and inferential aspects of one of Imam Reza’s (pbuh) hadiths, in which the rational argument for caution or rationality is beautifully clarified. Given the gap in previous research, which has primarily focused on generalities and has paid less attention to a comprehensive document and inferential analysis of this narration, this study seeks to assess the reliability of the narration using a descriptive-analytical method. The findings reveal that although the narration is considered weak by later standards of documentation, it remains trustworthy and acceptable due to certain indicators of reliability. In terms of inference, through logical reasoning and the rational argument for caution, it is demonstrated that choosing faith in God and adhering to religious commandments, even in uncertain circumstances, is the most rational choice and has a significant impact on human destiny. This concept can be used as a strong point in theological discussions to reinforce believers' faith and commitment to their beliefs, as well as to contribute to debates in theology.